2002
DOI: 10.1046/j.1365-2133.2002.04835.x
|View full text |Cite
|
Sign up to set email alerts
|

Guidelines for the management of bullous pemphigoid

Abstract: These guidelines have been prepared for dermatologists on behalf of the British Association of Dermatologists. They present evidence-based guidance for treatment, with identification of the strength of evidence available at the time of preparation of the guidelines and a brief overview of epidemiological aspects, diagnosis and investigation. The guidelines reflect data available from Medline, Embase, the Cochrane library, literature searches and the experience of the authors of managing patients with bullous p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
103
1
25

Year Published

2003
2003
2013
2013

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 131 publications
(130 citation statements)
references
References 47 publications
1
103
1
25
Order By: Relevance
“…6 mg/kg/day in moderate disease, and 50-70 mg or 0. 75-1 mg/kg/day in severe disease (Wojnarowska 2002). …”
Section: Systemic Steroid Therapymentioning
confidence: 99%
“…6 mg/kg/day in moderate disease, and 50-70 mg or 0. 75-1 mg/kg/day in severe disease (Wojnarowska 2002). …”
Section: Systemic Steroid Therapymentioning
confidence: 99%
“…Previous studies have identified a number of negative prognostic factors, such as age, low Karnofsky performance score and use of corticosteroids [16,18,19]. Immunosuppressive agents, systematic use of which has not been validated, may also affect the mortality rate [20]. …”
Section: Introductionmentioning
confidence: 99%
“…Recognizing this form of BP is important, since a high suspicion rate, extended and repeated diagnostic procedures are prerequisites for establishing the diagnosis of BP. Once the diagnosis is made, appropriate therapy of secondary infection and of BP along the proposed guidelines [33] will usually be successful.…”
Section: Discussionmentioning
confidence: 99%